Electrochromic device and method for manufacturing the same, electrochromic apparatus
Patent Information
- Application Number
- CN202610753714.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-28
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]电致变色器件通常包括导电聚合物,导电聚合物主要是一类芳香类化合物的聚合物,其中,聚吡咯(PPy)因其独特的分子结构而展现出优异的性能,但是,由于吡咯单体聚合时大多在3位和4位进行聚合,得到的聚吡咯3,4位C-C偶联缺陷较多,从而影响电致变色器件的长期稳定性,同时吡咯单体聚合得到的聚吡咯在有机溶剂中的溶解性相对较差,最终难以形成均匀的聚合物膜层或形成的聚吡咯膜层的质量不佳,进一步会影响其长期稳定性,以及相关技术中电致变色器件的制备方法存在工艺复杂且不环保等问题
[0005]本申请使用导电基底作为工作电极,使聚合反应进行时共聚物在导电基底上原位生长,从而能够增强共聚物膜层与导电基底之间的结合力,进而保证制备得到的电致变色器件具有优异的机械稳定性;另一方面,本申请的制备过程中使用水作为溶剂,更加绿色环保,成本较低且吡咯在水溶剂中容易达到稳定均匀的溶解状态,因此,在后续的聚合过程中容易在导电基底上直接形成均匀的膜层;同时本申请的电致变色器件的制备方法较为简单。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of electrochromic materials technology, specifically to electrochromic devices and their preparation methods, and electrochromic apparatus. Background Technology
[0002] Electrochromism refers to the phenomenon where the optical properties of electroactive materials, including transmittance, reflectance, and color, undergo reversible changes under an alternating electric field. The principle of electrochromism is that the solute on the thin film or surface of an electroactive substance (an electron acceptor / donor in an oxidized / reduced state) undergoes interconversion between oxidized and reduced states through electron migration at the electrode. The difference in photon absorption by electrons corresponding to the energy bands of the oxidized / reduced states causes the material to exhibit different colors.
[0003] Electrochromic devices typically incorporate conductive polymers, primarily aromatic compounds. Among these, polypyrrole (PPy) exhibits excellent properties due to its unique molecular structure. However, because pyrrole monomer polymerization often occurs at the 3- and 4-positions, the resulting polypyrrole exhibits numerous CC coupling defects at these positions, affecting the long-term stability of the electrochromic device. Furthermore, the polypyrrole obtained from monomer polymerization has relatively poor solubility in organic solvents, making it difficult to form a uniform polymer film or resulting in a poor-quality polypyrrole film, further impacting its long-term stability. Additionally, current methods for fabricating electrochromic devices suffer from complex processes and environmental concerns. Therefore, there is an urgent need to develop an environmentally friendly and simple method for fabricating electrochromic devices. Summary of the Invention
[0004] This application aims to at least partially address one of the technical problems in the related art. Therefore, one objective of this application is to propose a... The first aspect of this application discloses a method for fabricating an electrochromic device, comprising: A preparation solution is formed by dissolving pyrrole monomer, a monomer containing an aromatic structure, and an electrolyte in water; The preparation solution is polymerized on a conductive substrate to obtain a functional conductive layer containing a copolymer film layer; An electrochromic device is obtained by providing a counter electrode layer on the side surface of the functional conductive layer near the copolymer film layer, and filling the space between the functional conductive layer and the counter electrode layer with an electrolyte.
[0005] This application uses a conductive substrate as the working electrode, enabling the copolymer to grow in situ on the conductive substrate during the polymerization reaction. This enhances the bonding force between the copolymer film and the conductive substrate, thereby ensuring that the prepared electrochromic device has excellent mechanical stability. On the other hand, the preparation process of this application uses water as a solvent, which is more environmentally friendly and has a lower cost. Pyrrole can easily achieve a stable and uniform dissolution state in an aqueous solvent. Therefore, it is easy to directly form a uniform film on the conductive substrate during the subsequent polymerization process. At the same time, the preparation method of the electrochromic device of this application is relatively simple.
[0006] In some embodiments of this application, the method for fabricating the electrochromic device satisfies at least one of the following conditions: The molar ratio of the pyrrole monomer to the 3,4-ethylenedioxythiophene monomer is 3:2 to 17:2. The molar concentration of the pyrrole monomer in the preparation solution is 0.05 mol / L to 0.4 mol / L; The concentration of the electrolyte in the preparation solution is 0.1 mol / L to 1 mol / L; The pH of the preparation solution is 0~3; The electrolyte includes at least one of sodium chloride, sodium sulfate, sodium perchlorate, sodium fluoride, sodium p-toluenesulfonate, potassium chloride, potassium nitrate, potassium hydroxide, dipotassium hydrogen phosphate, lithium tetrafluoroborate, lithium hexafluoroborate, lithium perchlorate, hydrochloric acid, sulfuric acid, phosphoric acid, and phosphoric acid. The monomer containing an aromatic structure includes at least one of 3,4-ethylenedioxythiophene, aniline, and carbazole.
[0007] In some embodiments of this application, causing the preparation solution to undergo a polymerization reaction on a conductive substrate includes: Using the conductive substrate as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum wire as the counter electrode, a voltage is applied to the working electrode to induce a polymerization reaction in the preparation solution.
[0008] In some embodiments of this application, at least one of the following conditions is satisfied: The applied voltage is 0.01V~8V; The current density of the polymerization reaction is 0.3 mA·cm⁻¹. -2 ~15 mA·cm -2 ; The polymerization reaction takes 10s to 200s; The polymerization reaction temperature is 10℃~50℃, preferably 20℃~35℃; The shortest distance between the counter electrode and the working electrode is 2cm to 6cm.
[0009] The conductive substrate includes a base layer and a conductive layer disposed on one surface of the base layer, wherein the conductive layer includes at least one of fluorine-doped tin oxide, antimony-doped tin oxide, tin-doped indium oxide, molybdenum-doped indium oxide, gallium-doped zinc oxide, propylene carbonate, polyethylene terephthalate, polyimide, polyvinylidene fluoride, carbon nanotubes, silver nanowires, and graphene; preferably fluorine-doped tin oxide, antimony-doped tin oxide, or tin-doped indium oxide, and the base layer includes glass.
[0010] In some embodiments of this application, after the preparation solution undergoes a polymerization reaction on a conductive substrate, and before a counter electrode layer is formed on the surface of the functional conductive layer near the copolymer film layer, the process further includes: post-processing of the functional conductive layer, the post-processing including: The functional conductive layer is sequentially rinsed and calcined.
[0011] In some embodiments of this application, at least one of the following conditions is satisfied: The rinsing process includes washing the functional conductive layer with water 1 to 5 times. The calcination includes calcining the functional conductive layer at 50℃~200℃ for 2~12 hours.
[0012] In some embodiments of this application, the thickness of the copolymer film layer on the functional conductive layer is 80 nm to 800 nm.
[0013] In some embodiments of this application, the copolymer film layer includes [PPy] + (A - )-EDOT] n 、[PPy + (A - )-ANI] n 、[PPy + (A - )-CARB] n At least one of them; Where n is a positive integer from 100 to 1000, representing the degree of polymerization of the copolymer. A - It includes at least one of p-toluenesulfonate, perchlorate, and ethyl benzothiadiazole.
[0014] In a second aspect, this application provides an electrochromic device obtained by the aforementioned fabrication method. Consequently, this electrochromic device exhibits excellent mechanical stability and charge transport characteristics.
[0015] A third aspect of this application provides an electrochromic device, including the aforementioned electrochromic component. Therefore, this electrochromic device possesses excellent mechanical stability and charge transport characteristics. Attached Figure Description
[0016] Figure 1 This is a grazing incidence XRD phase diagram of the pyrrole-3,4-ethylenedioxythiophene copolymer in Example 1 of this application.
[0017] Figure 2 This is a grazing incidence X-ray scattering spectrum of the pyrrole-3,4-ethylenedioxythiophene copolymer in Example 1 of this application.
[0018] Figure 3 This is the Raman spectrum of the pyrrole-3,4-ethylenedioxythiophene copolymer in Example 1 of this application.
[0019] Figure 4 This is an atomic force microscope image of the pyrrole-3,4-ethylenedioxythiophene copolymer in Example 1 of this application.
[0020] Figure 5 This is a chronocurrent curve recorded during the electrochemical polymerization process of Example 1 of this application.
[0021] Figure 6 This is the electrochemical cyclic voltammogram of the electrochromic device prepared in Example 1 of this application.
[0022] Figure 7 This is a graph showing the electrochromic stability of the electrochromic device prepared in Example 1 of this application in 1 M LiClO4 medium.
[0023] Figure 8 This is a graph showing the electrochromic stability of the electrochromic device prepared in Example 1 of this application in 1 M LiClO4 medium.
[0024] Figure 9 This is a graph showing the electrochromic performance of the electrochromic device prepared in Example 1 of this application in 1 M LiClO4 medium.
[0025] Figure 10 This is a graph showing the electrochromic stability of the electrochromic device prepared in Comparative Example 1 of this application in 1 M LiClO4 medium.
[0026] Figure 11 This is a graph showing the electrochromic stability of the electrochromic device prepared in Comparative Example 2 of this application in 1 M LiClO4 medium.
[0027] Figure 12 This is a graph showing the electrochromic stability of the electrochromic device prepared in Comparative Example 3 of this application in 1 M LiClO4 medium.
[0028] Figure 13The images show the Raman spectrum (left) of the electrochromic thin film prepared in Comparative Example 4 of this application and the electrochromic stability performance (right) of the electrochromic device in 1 M LiClO4 medium. Detailed Implementation
[0029] The embodiments of this application are described in detail below. The embodiments described below are exemplary and intended to explain this application, and should not be construed as limiting this application.
[0030] This application is based on the applicant's following findings and insights: On the one hand, polypyrrole, due to its five-membered aromatic heterocycle, active nitrogen atom, and α-site in its molecular structure, readily forms free radical pyrrole groups, exhibiting excellent charge transport properties and semiconductor characteristics. Simultaneously, polypyrrole not only possesses advantages such as readily available raw materials and good environmental stability, but also displays significant color changes (yellow-green) under different electrochemical redox states. (Blue-purple) is a typical anodic electrochromic material. Pyrrole is the monomer that makes up polypyrrole. The cyclic structure of a pyrrole monomer has 5 carbon atoms, corresponding to positions 1, 2, 3, 4, and 5. Among them, positions 2 and 5 are α positions, and positions 3 and 4 are β positions. Ideally, pyrrole monomers are connected only at the α positions, forming a long and continuous conjugated double bond backbone, which is the basis for the conductivity and color change of polypyrrole. However, in the actual polymerization process, pyrrole monomers may be incorrectly connected at the α and β positions (i.e., poor α-β coupling), thereby disrupting the continuity of the conjugated double bond backbone. This results in more defects and poor stability in the final polypyrrole, thus affecting the stability of polypyrrole-based electrochromic devices. On the other hand, the solvents used in the preparation methods of electrochromic devices in related technologies are mostly organic solvents, and the preparation process is relatively complex, leading to problems such as high preparation costs and poor environmental friendliness.
[0031] Based on the above understanding, the inventors considered introducing other monomers during the polymerization process to control the reaction sites of the monomers in the polymerization reaction, thereby ensuring that the pyrrole monomers are linked only at the α-position, and polymerizing to obtain electrochromic copolymers with excellent performance, ultimately obtaining electrochromic devices with high stability; at the same time, they considered using environmentally friendly solvents for preparation without affecting the performance of the electrochromic device.
[0032] Therefore, in the first aspect of this application, a method for fabricating an electrochromic device is proposed, comprising: S10: Dissolve pyrrole monomer, aromatic monomer and electrolyte in water to form a preparation solution.
[0033] In this step, water is used as the solvent for the preparation solution, which is more environmentally friendly and less expensive than organic solvents. Pyrrole easily achieves a stable and uniform dissolution in aqueous solution, thus facilitating the direct formation of a uniform film on the conductive substrate during subsequent polymerization. Furthermore, water as a solvent aids in subsequent drying and washing processes. On the other hand, the introduction of monomers containing aromatic structures can guide the preferential linkage of pyrrole monomers at the α-position, reducing undesirable α-β coupling defects and ensuring the continuity of the conjugated backbone. For example, the monomers containing aromatic structures can be at least one of 3,4-ethylenedioxythiophene (EDOT), aniline (ANI), and carbazole (CARB).
[0034] In some embodiments, the mixing method of pyrrole monomer, monomer containing aromatic structure, electrolyte and water is not limited, and can be mixed according to actual conditions to ensure that the components in the preparation solution are uniform.
[0035] In some embodiments, the molar concentration of pyrrole monomer in the preparation solution is 0.05 mol / L to 0.4 mol / L, specifically, it can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, etc. The concentration of pyrrole monomer directly affects the polymerization rate. Within the above range, the subsequent polymerization reaction can be ensured to be in a stable and controllable state. At the same time, the above concentration can also ensure that the thickness, porosity, and conductivity of the resulting copolymer film reach the target range.
[0036] In some embodiments, the molar ratio of pyrrole monomer to monomer containing aromatic structure is (3:2) to (17:2), specifically, it can be 3:2, 5:2, 7:2, 9:2, 11:2, 13:2, 15:2, 17:2, or any range between the two. By precisely controlling the molar ratio, the pyrrole monomer can be preferentially linked at the α-position, minimizing undesirable α-β coupling defects, thereby laying the foundation for obtaining high-performance electrochromic devices.
[0037] In some embodiments, the concentration of the electrolyte in the preparation solution is 0.1 mol / L to 1 mol / L, specifically, it can be 0.1 mol / L, 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1 mol / L, or any range between two of these. The core function of the electrolyte is to provide an ionic conductivity pathway for electropolymerization. An electrolyte concentration within the aforementioned range allows the subsequent polymerization reaction to proceed at a stable and controllable rate, thereby enabling the monomer to polymerize uniformly on the conductive substrate surface, forming a copolymer film of uniform thickness and dense structure.
[0038] Specifically, the electrolyte includes at least one of sodium chloride, sodium sulfate, sodium perchlorate, sodium fluoride, sodium p-toluenesulfonate, potassium chloride, potassium nitrate, potassium hydroxide, dipotassium hydrogen phosphate, lithium tetrafluoroborate, lithium hexafluoroborate, lithium perchlorate, hydrochloric acid, sulfuric acid, phosphoric acid, and phosphoric acid. These electrolytes are widely available, inexpensive, and easy to wash, further enhancing their environmental friendliness. They are also highly soluble in water, perfectly suited to the aqueous solvent system of this application. Furthermore, these electrolytes completely dissociate into highly mobile ions in aqueous solution, efficiently conducting charge and providing a stable conductive environment for the subsequent electropolymerization reaction. When using the above electrolytes to prepare the solution, the pH of the solution must be between 0 and 3, specifically 0, 1, 2, 3, or any two of these ranges. Pyrrole monomers tend to couple at the α-position under strongly acidic conditions, effectively suppressing undesirable α-β coupling, thus ensuring the conjugated continuity of the copolymer backbone, reducing structural defects, and improving the stability of the electrochromic properties. Furthermore, a strongly acidic environment can enhance the oxidative reactivity of pyrrole with monomers containing aromatic structures, thereby further improving the efficiency of the polymerization reaction. Therefore, those skilled in the art can select different electrolytes as needed.
[0039] In some embodiments, the prepared solution can be treated with nitrogen to obtain a nitrogen-saturated prepared solution, thereby removing dissolved oxygen from the prepared solution and thus avoiding interference from dissolved oxygen to the subsequent polymerization reaction.
[0040] S20: The preparation solution is polymerized on a conductive substrate to obtain a functional conductive layer containing a copolymer film.
[0041] In this step, a three-electrode system is used for the polymerization reaction. Specifically, a conductive substrate is used as the working electrode, a saturated calomel electrode is used as the reference electrode, and a platinum wire is used as the counter electrode. A voltage is applied to the working electrode to cause the preparation solution to undergo a polymerization reaction. Pyrrole monomers and monomers containing aromatic structures undergo a polymerization reaction to generate copolymers. These copolymers are deposited on the conductive substrate to form a functional conductive layer containing a copolymer film.
[0042] When the aromatic monomer is EDOT, the polymer film layer includes [PPy]. + (A - )-EDOT] n When the aromatic monomer is ANI, the polymer film layer includes [PPy]. + (A - )-ANI] n When the aromatic monomer is CARB, the polymer film layer includes [PPy]. + (A - )-CARB] nWhere n is a positive integer from 100 to 1000, representing the degree of polymerization of the copolymer.
[0043] Furthermore, A in the above chemical formula - A is the anion in pyrrole monomers. - It includes at least one of p-toluenesulfonate, perchlorate, and ethyl benzothiadiazole.
[0044] For example, when the two monomers are pyrrole and EDOT, they are polymerized under specific conditions to obtain the pyrrole-3,4-ethylenedioxythiophene copolymer shown in Formula 1. Specifically, the thiophene monomer is blocked in the polypyrrole molecular chain.
[0045] Formula 1 In some embodiments, the conductive substrate includes a base layer and a conductive layer disposed on one surface of the base layer. The conductive layer comprises at least one of fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), molybdenum-doped indium oxide (IMO), gallium-doped zinc oxide (GZO), propylene carbonate (PC), polyethylene terephthalate (PET), polyimide (PI), polyvinylidene fluoride (PVDF), carbon nanotubes, silver nanowires, and graphene; preferably fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), or tin-doped indium oxide (ITO). The base layer comprises glass. This application uses a conductive substrate as the working electrode, allowing pyrrole-3,4-ethylenedioxythiophene copolymer to grow in situ on the conductive substrate during the polymerization reaction, thereby enhancing the adhesion between the pyrrole-3,4-ethylenedioxythiophene copolymer film and the conductive substrate. This ensures that the electrochromic device possesses excellent mechanical stability and charge transport performance.
[0046] In some embodiments, the voltage applied to the working electrode during the polymerization reaction is 0.01V to 8V, specifically 0.01V, 0.5V, 1V, 2V, 4V, 6V, 8V, etc. This voltage range falls within the oxidation potential range of the pyrrole monomer and the EDOT monomer, ensuring that the two monomers undergo synchronous and stable oxidative polymerization on the working electrode surface and guaranteeing block polymerization to obtain the polymer structure of Formula 1 mentioned above. If the voltage is too low, the monomers may not be effectively oxidized, making the polymerization reaction difficult to proceed; if the voltage is too high, side reactions may occur, leading to problems such as excessive monomer oxidation and increased defects in the film structure.
[0047] In some embodiments, the current density of the three-electrode system during the polymerization reaction is 0.3 mA·cm⁻¹. -2 ~15mA·cm -2 Specifically, it can be 0.3 mA·cm -2 1mA·cm-2 2mA·cm -2 5mA·cm -2 7mA·cm -2 10mA·cm -2 12mA·cm -2 15mA·cm -2 The current density affects the oxidation rate of the monomer. A current density within the above range helps to ensure that the oxidation rate of the monomer is within the target range, thereby ensuring a stable and uniform formation of the copolymer film.
[0048] In some embodiments, the polymerization reaction time is 10s to 200s, specifically 10s, 20s, 50s, 80s, 100s, 120s, 150s, 180s, 200s, etc. The polymerization reaction time can be controlled according to actual needs (the thickness of the copolymer film).
[0049] In some embodiments, the polymerization temperature is 10°C to 50°C, specifically 20°C to 35°C. Exemplary values include 10°C, 20°C, 30°C, 40°C, and 50°C. This temperature range ensures mild polymerization conditions and allows for stable oxidative polymerization of the two monomers. It largely avoids excessive monomer oxidation or side reactions that might occur at excessively high polymerization temperatures, while excessively low temperatures could lead to reduced polymerization efficiency.
[0050] In some embodiments, the shortest distance between the counter electrode and the working electrode is 2cm to 6cm, and exemplary distances can be 2cm, 3cm, 4cm, 5cm, 6cm, etc. This spacing allows for a more uniform electric field distribution between the electrodes, thereby ensuring uniform deposition of the copolymer film on the conductive substrate surface. It largely avoids problems such as localized current concentration caused by excessively close distances between the counter electrode and the working electrode, or insufficient current density caused by excessively large distances.
[0051] In some embodiments, after the polymerization reaction is completed, the functional conductive layer can be post-treated, including washing and calcining the functional conductive layer in sequence.
[0052] Specifically, the functional conductive layer can be washed 1 to 5 times with deionized water. Calcination involves maintaining the functional conductive layer at 50°C to 200°C (calcination atmosphere such as air, vacuum, nitrogen, helium, etc.) for 2 to 12 hours to enhance the crystallinity of the thin film functional layer, which is beneficial to improving its mechanical and electrochemical stability.
[0053] In some embodiments, the prepared functional conductive layer includes a conductive substrate and a copolymer film layer deposited on the surface of the conductive substrate. Specifically, the thickness of the copolymer film layer is 80 nm to 800 nm, and exemplary values can be 80 nm, 100 nm, 130 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, etc. A copolymer film layer thickness within the above range can generally ensure that the electrochromic device has excellent performance.
[0054] S30: A counter electrode layer is disposed on the side surface of the functional conductive layer near the copolymer film layer, and an electrolyte is filled between the functional conductive layer and the counter electrode layer to obtain an electrochromic device.
[0055] In this step, for example, a pure polypyrrole film can be used to cover the ITO surface to form a counter electrode layer, which is superimposed on the functional conductive layer. A certain amount of LiClO4 / PC solution is filled between the two layers, and then the layers are sealed and assembled to finally form an electrochromic device.
[0056] In a second aspect of this application, an electrochromic device is proposed, which is obtained by the aforementioned preparation method. Therefore, this electrochromic device possesses all the advantages of the preparation method for the electrochromic device described above, which will not be elaborated upon here.
[0057] A third aspect of this application provides an electrochromic device, including the aforementioned electrochromic apparatus. Therefore, this electrochromic device exhibits excellent stability and charge transport characteristics.
[0058] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or in accordance with the product manual.
[0059] Example 1 A standard three-electrode system was selected from the Shanghai Chenhua (760E) electrochemical workstation. The working electrode was ITO glass, the reference electrode was a saturated calomel electrode (SCE, 3 M KCl), and the counter electrode was a platinum wire electrode (Pt). Sodium p-toluenesulfonate (NaTSO), dipotassium hydrogen phosphate (K₂HPO₄), and sodium fluoride (NaF) electrolytes were dissolved in 20 ml of deionized water to prepare 0.10 mol / L solutions. -1 K2HPO4, 0.10 mol L -1 TSONa, 0.05 mol L -1The NaF mixed electrolyte solution, using 0.50 mol / L -1 The pH of the mixed solution was adjusted to 1 ± 0.02 with hydrochloric acid to create an acidic environment. Pyrrole (Py) monomer and 3,4-ethylenedioxythiophene (EDOT) monomer were then added sequentially to the mixed electrolyte solution, ultimately forming a solution containing 0.05 mol / L... -1 Py and 0.02 mol L -1 Preparation solution of EDOT; Before electrochemical polymerization, the working electrode ITO needs to be ultrasonically cleaned for 20 min in 25 mL of anhydrous acetone, 25 mL of anhydrous ethanol and 25 mL of deionized water, respectively, and then dried with N2 flow. The polymerization voltage was controlled at 0.9 V (relative to SCE) and the polymerization current at 6 mA·cm⁻¹ during the polymerization reaction. -2 The polymerization time was 25 seconds, and the polymerization temperature was 25℃. After the polymerization deposition process is completed, the residual preparation liquid on the surface of the copolymer film is removed by deionized water droplet coating, and then the film is naturally air-dried in the air at room temperature for 2 hours to obtain the functional conductive layer. A functional conductive layer is superimposed on a counter electrode layer covering a pure polypyrrole film, and an electrolyte layer of LiClO4 / PC is filled between the functional conductive layer and the counter electrode layer, thus assembling an electrochromic device.
[0060] Example 2 Similar to Example 1, the main difference is that pyrrole (Py) monomer and 3,4-ethylenedioxythiophene (EDOT) monomer were added sequentially to the mixed electrolyte solution, ultimately forming a solution containing 0.05 mol / L... -1 Py and 0.01 mol L -1 EDOT preparation solution.
[0061] Example 3 Same as Example 1, the main difference being: the polymerization current was controlled at 0.3 mA·cm during the polymerization reaction. -2 The aggregation time is 30 seconds.
[0062] Example 4 Similar to Example 1, the main difference is that the control potential is stepped between 0.9 V and 0.8 V, the step time is set to 5s, and it continues for 3 step cycles.
[0063] Example 5 Same as Example 1, the main difference being that the molar ratio of pyrrole (Py) monomer to 3,4-ethylenedioxythiophene (EDOT) monomer is 3:2. Specifically, the final product contains 0.15 mol L -1 Py and 0.1 mol L -1The preparation solution of EDOT was prepared at a polymerization temperature of 10℃.
[0064] Example 6 Same as Example 1, the main difference being that the molar ratio of pyrrole (Py) monomer to 3,4-ethylenedioxythiophene (EDOT) monomer is 17:2. Specifically, the final product contains 0.4 mol L... -1 Py and 0.047 mol L -1 The preparation solution of EDOT was prepared at a polymerization temperature of 50°C.
[0065] Example 7 Same as Example 1, the main difference being: hydrochloric acid was dissolved in 20 ml of deionized water to prepare a solution containing 1 mol L... -1 The pH of the prepared solution is 0±0.02 after the monomer is added to the mixed solution of hydrochloric acid.
[0066] Example 8 Same as Example 1, the main difference being: hydrochloric acid was dissolved in 20 ml of deionized water to prepare 0.001 mol L... -1 The pH of the prepared solution is 3 ± 0.02 after the monomer is added to the mixed solution of hydrochloric acid.
[0067] Comparative Example 1 Same as Example 1, the main difference being: 3,4-ethylenedioxythiophene (EDOT) monomer was added to the mixed electrolyte solution, ultimately forming a solution containing 0.01 mol L... -1 Preparation solution of EDOT; The polymerization voltage was controlled at 1.2 V (relative to SCE) and the polymerization current at 2.5 mA·cm during the polymerization reaction. -2 The aggregation time is 30 seconds.
[0068] Comparative Example 2 Same as Example 1, the main difference being: pyrrole (Py) monomer was added to the mixed electrolyte solution, ultimately forming a solution containing 0.15 mol L... -1 Preparation solution of Py; The polymerization voltage was controlled at 0.75V (relative to SCE) and the polymerization current at 5 mA·cm during the polymerization reaction. -2 The aggregation time is 20 seconds.
[0069] Comparative Example 3 Same as Example 1, the main difference is that acetonitrile is used as the solvent in the preparation solution.
[0070] Comparative Example 4 Similar to Example 1, the main difference is that acetonitrile is used as a solvent in the preparation solution. Potassium hydroxide is dissolved in acetonitrile to obtain a mixed solution, and then the monomer is added to make the pH of the preparation solution 11±0.02.
[0071] Test methods Cyclic voltammetry and long-cycle performance testing were performed using cyclic voltammetry and multi-potential step technology on an electrochemical workstation, respectively. The electrochromic device served as the working electrode, and the Pt wire electrode served as the counter electrode. Parameters such as scan rate and voltage window were set for cyclic voltammetry testing, and parameters such as potential and number of steps were set for long-cycle multi-potential step testing.
[0072] Test results The pyrrole-3,4-ethylenedioxythiophene copolymer film obtained by the polymerization reaction in Example 1 was subjected to XRD phase analysis, X-ray diffraction, and force microscopy tests. Specifically, Figure 1 and Figure 2 These are the grazing incidence XRD phase diagram and grazing incidence X-ray scattering spectrum of the copolymer film, respectively. Figure 1 and Figure 2 It can be seen that the copolymer has a high degree of crystallinity; Figure 3 The image shows the Raman spectrum of the copolymer film, exhibiting the characteristic peaks of the polypyrrole-ethylene dioxythiophene copolymer. Figure 4 This is an atomic force microscopy image of the copolymer film, revealing an open, porous dendritic structure. Top-view imaging confirms that a three-dimensional dendritic network uniformly covers the ITO substrate. The film contains a dense inner layer (approximately 30 nm thick), from which a dendritic structure grows, which can be divided into primary dendrites (approximately 100 nm in height) and finer secondary branches (approximately 5–9 nm in thickness). This hierarchical morphology helps release residual stress, thereby enhancing the film's stability.
[0073] The current during the polymerization reaction process in Example 1 was recorded, see... Figure 5 It can be seen that the thin film undergoes a rapid electrochemical polymerization process on the ITO conductive substrate in a short period of time, involving crystal nucleation, epitaxial growth, and film formation.
[0074] Cyclic voltammetry tests were performed on the electrochromic device of Example 1, and the cyclic voltammetry curves are shown in the figure. Figure 6 An electrochromic device was used as the working electrode, and a platinum wire electrode as the counter electrode, and the test was conducted in an electrolytic cell. The scan rate was set to 10 mV / s. -1 The voltage window is -1.2 to 0.9 V. Figure 6 It can be seen that a distinct oxidation peak at -0.12V can be observed in the forward scan of -1.2 to 0.9V, and the corresponding reduction peak appears in the reverse scan. During this process, the copolymer film shows a color change from bright yellow to yellowish-brown to gray to bluish-black.
[0075] Cyclic performance tests were performed on the electrochromic device of Example 1, with cycles of 9300 and 27900 cycles respectively. The long-cycle stability test results under different potential steps are shown in [Figure 1]. Figure 7 and Figure 8 It can be seen that the electrochromic device of this application has excellent cycle stability; at the same time, the color switching response speed of the electrochromic device during cycling is very fast, with both coloring and fading times less than 1 second. Figure 9 This demonstrates that electrochromic devices possess excellent electrochemical activity.
[0076] Cyclic performance tests were conducted on the electrochromic devices of Comparative Examples 1 to 4, and the test results are shown in the table below. Figures 10-13 It can be seen that significant performance degradation occurred after cycling, indicating poor stability. The electrochromic color change was not obvious, and the copolymer film layer was easily detached from the ITO substrate during the test.
[0077] In the description of this application, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0078] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0079] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A method for fabricating an electrochromic device, characterized in that, include: A preparation solution is formed by dissolving pyrrole monomer, a monomer containing an aromatic structure, and an electrolyte in water; The preparation solution is polymerized on a conductive substrate to obtain a functional conductive layer containing a copolymer film layer; An electrochromic device is obtained by providing a counter electrode layer on the side surface of the functional conductive layer near the copolymer film layer, and filling the space between the functional conductive layer and the counter electrode layer with an electrolyte.
2. The preparation method according to claim 1, characterized in that, At least one of the following conditions must be met: The molar ratio of the pyrrole monomer to the monomer containing the aromatic structure is 3:2 to 17:2; The molar concentration of the pyrrole monomer in the preparation solution is 0.05 mol / L to 0.4 mol / L; The concentration of the electrolyte in the preparation solution is 0.1 mol / L to 1 mol / L; The pH of the preparation solution is 0~3; The electrolyte includes at least one of sodium chloride, sodium sulfate, sodium perchlorate, sodium fluoride, sodium p-toluenesulfonate, potassium chloride, potassium nitrate, potassium hydroxide, dipotassium hydrogen phosphate, lithium tetrafluoroborate, lithium hexafluoroborate, lithium perchlorate, hydrochloric acid, sulfuric acid, phosphoric acid, and phosphoric acid. The monomer containing an aromatic structure includes at least one of 3,4-ethylenedioxythiophene, aniline, and carbazole.
3. The preparation method according to claim 1, characterized in that, The polymerization reaction of the preparation solution on a conductive substrate includes: Using the conductive substrate as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum wire as the counter electrode, a voltage is applied to the working electrode to induce a polymerization reaction in the preparation solution.
4. The preparation method according to claim 3, characterized in that, At least one of the following conditions must be met: The applied voltage is 0.01V~8V; The current density of the polymerization reaction is 0.3 mA·cm⁻¹. -2 ~15 mA·cm -2 ; The polymerization reaction takes 10s to 200s; The polymerization reaction temperature is 10℃~50℃, preferably 20℃~35℃; The shortest distance between the counter electrode and the working electrode is 2cm to 6cm; The conductive substrate includes a base layer and a conductive layer disposed on one surface of the base layer, wherein the conductive layer includes at least one of fluorine-doped tin oxide, antimony-doped tin oxide, tin-doped indium oxide, molybdenum-doped indium oxide, gallium-doped zinc oxide, propylene carbonate, polyethylene terephthalate, polyimide, polyvinylidene fluoride, carbon nanotubes, silver nanowires, and graphene; preferably fluorine-doped tin oxide, antimony-doped tin oxide, or tin-doped indium oxide, and the base layer includes glass.
5. The preparation method according to claim 1, characterized in that, After the preparation solution undergoes a polymerization reaction on a conductive substrate, and before a counter electrode layer is formed on the surface of the functional conductive layer near the copolymer film layer, the process further includes: performing a post-treatment on the functional conductive layer, the post-treatment including: The functional conductive layer is sequentially rinsed and calcined.
6. The preparation method according to claim 5, characterized in that, At least one of the following conditions must be met: The rinsing process includes washing the functional conductive layer with water 1 to 5 times. The calcination includes calcining the functional conductive layer at 50℃~200℃ for 2h~12h.
7. The preparation method according to any one of claims 5 to 6, characterized in that, The thickness of the copolymer film on the functional conductive layer is 80 nm to 800 nm.
8. The preparation method according to claim 7, characterized in that, The copolymer film layer includes [PPy] + (A - )-EDOT] n 、[PPy + (A - )-ANI] n 、[PPy + (A - )-CARB] n At least one of them; Where n is a positive integer from 100 to 1000, representing the degree of polymerization of the copolymer. A - It includes at least one of p-toluenesulfonate, perchlorate, and ethyl benzothiadiazole.
9. An electrochromic device, characterized in that, It is obtained by the preparation method described in any one of claims 1 to 8.
10. An electrochromic device, characterized in that, Including the electrochromic device as described in claim 9.